Digital Based Science Learning Through a Scientific Approach in Elementary School (Journal of Primary Education, 2022)
The rapid development science and technology can the main key in efforts to develop students’ self-ability in the field science. The existence technological developments have a great influence on the world of education. One of them is self-ability can apply, namely the application digital literacy. This study aims to determine student activities and the effectiveness learning science with a scientific approach through digital literacy in elementary schools. This research is experimental research. The sample this study consisted of fifth grade students at SDN Bringin 01 and SDN Tambakaji 03 Ngaliyan districts, using purposive sampling technique. It is a sampling technique with certain considerations. Through it researchers in terms of the achievements and competencies students in each class. This research data using questionnaires, tests, observations, interviews. The results analysis teacher needs given digital literacy were further validated by media experts and used learning in the experimental class and control class. Student learning activities showed differences acquisition student activity scores through non-digital media with 76.4 good results, while student activities through digital literacy showed results 82.4 very good categories. The effectiveness science learning with a scientific approach through digital literacy can improve the learning outcomes experimental class with an N-Gain value 0.7366 medium criteria, while the control class with N-Gain value 0.5656 high criteria. The results study can conclude that learning science with a scientific approach through digital literacy can improve elementary school students learning outcomes. In the end, it is hoped that similar research can carried out with other materials.